PENGARUH NILAI ADAT BATAK DALIHAN NA TOLU TERHADAP PREFERENSI MEMILIH PASANGAN CALON DALAM PEMILIHAN BUPATI DAN WAKIL BUPATI KABUPATEN TAPANULI UTARA DI KECAMATAN TARUTUNG TAHUN 2018 - Panjaitan, Nancy Lady; Sardini, Nur Hidayat (Journal of Politic and Government Studies, 2019)
This research was conducted to see the effect of Dalihan Na Tolu Batak customary values on the Regional Head Election by taking the location in Tarutung District, North Tapanuli Regency. The kinship system in Batak people is still very strong with Dalihan Na Tolu which includes Hula-Hula, Dongan Tubu, and Boru. The research method used is a quantitative method with an explanatory descriptive approach that explains the relationship between independent and bound variables from the research theme, namely explaining the position of the variables Hula-Hula, Dongan Tubu, Boru, and preference choosing and the relationship between variables one with other variables. The data is then processed using regression analysis techniques. To obtain data, the authors conducted data collection through a questionnaire where the population was 42.125 people in Tarutung Subdistrict. Questionnaires were distributed to the community through the determination of samples carried out by a simple random sampling method of 400 people. The results of the study can be concluded that there is a significant influence between Hula-Hula (X1) and preference choosing (Y), then there is the influence of Dongan Tubu (X2) with preference choosing (Y) and the influence of Boru (X3) on preference choosing (Y). The magnitude of the influence given by the variables Hula-Hula, Dongan Tubu, and Boru simultaneously on preference to choose is 35,3%. This means that 35,5% of the preference factors for choosing people in Tarutung Subdistrict in the Election of Regent and Deputy Regent of North Tapanuli Regency in 2018 were due to contributions from the variables Hula-Hula, Dongan Tubu, and Boru. Keywords : Influence, Dalihan Na Tolu, Choosing Preferences